Crescimento de tilápia-do-nilo (Oreochromis niloticus) alimentados com rações contendo extrato etanólico de oliveira (Olea europaea) - Souza, Déborah Andrade (2024)
The objective of this study was to evaluate four different treatments containing different concentrations of ethanolic extract of olive leaves incorporated into the feed (0%; 0.5%; 1.0% and 2.0%). We then evaluated the zootechnical performance and intestinal histology of juvenile tilapia. On day 0 and day 40, eight fish from each treatment were randomly chosen for biometry and weighing. The Nile tilapia (oreochromis niloticus) is a fish well adapted to tropical, subtropical and temperate climate countries despite being native to Africa and Palestine (EL SAYED, 2006). It is a species with high breeding potential due to its easy adaptation to management and different breeding methods (MICHELATO et al., 2016), and water quality, it has a high growth rate, resistance to diseases and easy reproduction (HE et al., 2013). Due to this, commercial tilapia farming has been gaining ground in the market and is increasingly appreciated for its white meat and absence of intramuscular spines (OLIVEIRA FILHO et al., 2010). The experiment was carried out with 180 juvenile Nile tilapia (oreochromis niloticus) weighing 1-5g distributed in 30 L water tanks equipped with an aeration system in a closed water recirculation system containing biological filters. The fish were divided into a completely randomized design (CRD) with 4 treatments and 3 replicates and fed twice a day (9 am and 5 pm) until apparent satiety. Immediately after, the tanks were siphoned to remove all food residue and supplemented with water under the same conditions. At the end of the study, analyses of zootechnical performance, growth and histology revealed a dose-dependent effect, demonstrating an increase in weight gain and villus height as the dose of the extract increased. No pathologies were found in the intestinal segments analyzed and there were no deaths during the experimental period. This dose-dependent result was probably due to oleuropein, the main phenolic compound present in olive leaves, affecting the neuromodulatory and neuroendocrine systems, which have a direct connection with the gastrointestinal tract, enzymatic factors and growth of intestinal enterocytes. Therefore, we recommend the use of 2.0% ethanolic extract of olive leaves added to the feed due to its positive dose-dependent effect.